Maternal health literacy among pregnant women in Indonesia: A qualitative study - Putri, Anggie Pradana; Hanifah, Lilik; AM, Ady Irawan.; Lu, Yu Ying (International Journal of Nursing and Health Services (IJNHS), 2023)
Introduction: Gaining insight into the maternal health literacy situation among pregnant women in Indonesia is crucial, as it forms the foundation for crafting precise interventions to enhance the well-being of mothers and infants on a national scale. Objective: This study aimed to explore the perspective of maternal health literacy among pregnant Indonesian women. Method: We employed a qualitative phenomenology method to explore maternal health literacy. Purposive sampling was used to collect participants' data. The data saturation was achieved at the thirteenth pregnant woman. The collected data were analyzed using Colaizzi's strategy to identify themes and subthemes within the phenomenon. Results: Four themes and seventeen subthemes emerged to explain maternal health literacy among pregnant women in this study. These themes include the ability to understand health-related information, search for information related to maternal health during pregnancy, assess and evaluate obtained information regarding pregnancy and maternal health, and decision-making, action, and maternal health behavior. Recommendation: The findings have the potential to benefit multiple sectors and contribute to efforts to improve maternal health in Indonesia. Culturally tailored health education programs, community engagement, empowerment, decision-making support, strengthening healthcare infrastructure, and integrating technology and telemedicine are all essential components